Poets, versifiours, and makeres: a study on the semantic field of poetry in Middle English - Mäihäniemi, Sanna (My University, 2021)
Middle English literature and the lexis of Middle English have both been studied extensively over the past decades. However, the semantic field of poetry has received less attention in earlier studies. Research in this field can reveal more about the development of this area of Middle English lexis as well as about the literature of the period and attitudes towards it. The aim of this thesis is to study the etymology of the data and semantic change. One aim is also to observe if changes in medieval English society and culture are reflected in the data. To collect the data, online dictionaries were utilised: the Middle English Dictionary, the Oxford English Dictionary, and the Historical Thesaurus of Oxford English Dictionary. These were chosen for their reliability and the large amount of data they provide. Using three different search terms, the data were collected in the Middle English Dictionary. The Historical Thesaurus of Oxford English Dictionary and its category of poetry-related lexical items were used to ensure that any relevant lexical items had not been missed. The Oxford English Dictionary was utilised for retrieving more detailed etymological information as well as for studying semantic change. Only such lexical items that occur both in the Middle English Dictionary and in the Oxford English Dictionary were included in the data of this study. The analysis of the data shows that the influence of French is significant in the semantic field of poetry. This finding strengthens the perception of French as a language that has strongly influenced medieval English literature. Some Latin influence as well as vocabulary inherited from Old English is visible in the data, too. The languages that influenced the semantic field of poetry in the Middle English period and the degree to which those languages affected the data are in line with earlier findings on the lexis of Middle English. The changes in society and culture that took place in medieval England impacted the data to some extent, for example when lexical items of a certain etymology had been adopted to this semantic field and what languages acted as major source languages. When it comes to semantic change, seven example cases were studied. The results show that, in most cases, the earliest sense of these lexical items occurs significantly prior to the development of the poetry-related sense. Furthermore, records of the use of one example case indicates that the use of the poetry-related sense was rare in the Middle English period. The two types of semantic change that occurred were specialisation and a metaphor.
Keywords: Middle English language, historical semantics, etymology